Sensitivity Analysis of Factors Affecting the Calibration of Heat-Flow-Meter Apparatus - Zarr, Robert R.; Carvajal, Sergio A.; Filliben, James J. (ASTM International, 2018)
Abstract The analysis and results of a sensitivity study of four procedural variables on the calibration response of two commercial heat-flow-meter apparatuses in conformance with ASTM Test Method C518, Standard Test Method for Steady-State Thermal Transmission Properties by Means of the Heat Flow Meter Apparatus, are presented. The apparatuses ranged in plate size from 305 mm by 305 mm to 610 mm by 610 mm and were calibrated using Standard Reference Materials 1450c, Fibrous Glass Board, and 1453, Expanded Polystyrene Board, issued by the National Institute of Standards and Technology. A major objective of the study is to rank the relative importance of the factors and interactions affecting the calibration of the apparatus. Seventy-six runs were conducted under input conditions that varied the mean temperatures from 17°C to 30°C, temperature differences from 17 K to 30 K, heat flow up or down across the specimen thickness, and different circulation bath temperatures. For each apparatus and SRM, the experiment followed a full factorial design for the four factors and included three interspatial replicates to assess for temporal drift. The study revealed that mean temperature and heat flow direction were the two most important test method factors affecting the calibration of both apparatuses. Although the temperature effect was the same for both apparatuses, the heat flow direction effect was found to be instrument dependent. The study also found that the calibration factor for each apparatus was affected by the reference material utilized for calibration. Empirically derived predictive models for each apparatus SRM combination are presented covering the experimental region defined by the input test conditions.